Use of assistive technology by students with dyslexia in post-secondary education. - Draffan EA; Evans DG; Blenkhorn P (Disability & Rehabilitation: Assistive Technology, 2007)
Purpose. To identify the types and mix of technology (hardware and software) provided to post-secondary students with dyslexia under the UK's Disabled Student Allowance (DSA), and to determine the students' satisfaction with, and use of, the equipment provided and to examine their experiences with training. Method. A telephone survey of 455 students with dyslexia who had received technology under the DSA from one equipment supplier was conducted over in the period September to December 2005. The survey obtained a mixture of quantitative data (responses to binary questions and selections from a five-point rating scale) and qualitative data (participants identifying positive and negative experiences with technology). In addition, the equipment supplier's database was used to determine the technology supplied to each of the participants. Result. Technology provision is variable between students. The majority of students receive a recording device, text-to-speech software and concept mapping tools in addition to a standard computer system. Ninety percent of participants are satisfied or very satisfied with the hardware and the software that they receive. A total of 48.6% of participants received training, with 86.3% of those expressing satisfaction with the training they received. Of those that were offered training but elected not to receive it, the majority did so because they felt confident about their IT skills. Conclusions. Students express satisfaction not only with the computer systems that they receive but also with the special-purpose software provided to support their studies. Significant numbers of students elect not to receive training and may, therefore, not be using their equipment to its best advantage.